EFFECT OF BRAND EQUITY AND PROMOTION TO PURCHASING DECISIONS OF HONDA MOTORCYCLE - Zumri Zuliyarso; Wahyu Hidayat; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2014)
Automotive business development in Indonesia is now characterized by wide variety competition which impact on consumer behavior changes in determining purchasing decisions ranging from product quality, product design structure, and promotions that offered towards consumer, even with big brand names attached to the product. In the conditions of strict competition on motorcycle dealer’s market, Tunggul Sakti Sejahtera Semarang dealer’s are trying to do their business policies to achieve the desired market share. Based on Honda motorcycle sales data on Tunggul Sakti Sejahtera Semarang dealer, there are sales not in accordance with the specified target. This study aims to determine how far the influence of brand equity and promotion of their Honda motorcycle purchasing decisions on the Tunggul Sakti Sejahtera Semarang dealer. This type of research is explanatory research using primary data through questionnaires and secondary data from website in the form of a percentage of sales of Honda motorcycles with other motorcycle brands. The population of research is consumers who make purchases Honda motorcycle at Tunggul Sakti Sejahtera Semarang dealer in 2008-2012 with a sample of 98 respondents from a population of 5356 people using purposive sampling technique. The sampling technique used was purposive sampling. The measurement using the Likert scale. Data analysis method used is descriptive qualitative that use validity and reliability test, Cross Tabulation Analysis (Crosstab), Coefficient of Correlation, Simple Linear Regression, Multiple Linear Regression, Coefficient of Determination, t-test and F-test with the SPSS software program. From the analysis found that the categories of the brand equity of 68.4 per cent expressed good. In categories of promotion, 56.1 percent known good states. variable Brand equity affect purchase decisions on the of 34.8 percent. Variable Promotion influence the purchasing decisions of 29.7 percent. Brand equity and promotion variables influence the purchasing decisions of 4.23 percent. So it can be concluded the better brand equity and promotion is expected to increase consumer purchasing decisions. The suggestions can be given in this study is, Tunggul Sakti Sejahtera Semarang need to increase promotional activities with sponsorship of musical events, sports events, and advertise through the local television media companies.